Effects of Whey Protein Coating Incorporated with Propolis-?-Cyclodextrin Emulsion on Quality of Refrigerated Sea Bass Fillets (Dicentrarchus labrax) - Fadiloglu, Eylem Ezgi; Coban, Ozlem Emir (Taylor & Francis Inc, 2022)
The effect of edible coating combining whey protein isolate (WPI) with Propolis/beta-cyclodextrin (beta CD) emulsion on quality of sea bass (Dicentrarchus labrax) fillets during 16 days of cold storage at 4 degrees C was investigated. coatings reduced pH value and weight loss. The TVB-N and TBA values of WPI-beta CD-Propolis coated samples were significantly (p < .05) lower than those of control and WPI-beta CD coated samples. WPI-beta CD-Propolis coatings were very effective in inhibiting bacterial growth and they prolonged the shelf life of sea bass fillets by 8 days. The color, odor, and texture scores of the WPI-beta CD-Propolis treated samples were significantly higher than that of control samples and WPI-beta CD samples (p < .05).
Keywords: Sea bass; whey protein isolate coating; propolis/beta-cyclodextrin emulsion; refrigerated storage quality